ANALISIS SIFAT MEKANIK PADA KOMPOSIT SERAT BATANG WIDURI _EPOXY DENGAN MENGGUNAKAN PENGUJIAN UJI TARIK - Ilham Yuhyi; Viktor Naubnome (Dinamika : Jurnal Ilmiah Teknik Mesin, 2022)
The term Fiber Reinforced Natural composite is now applied to a wide range of materials that are wholly or partly derived from renewable resources. Keeping up with technological developments is necessary to stop the development of materials that are not safe for the environment. The concept of renewable materials is now becoming very important because of the need to protect the natural environment. The widuri tree (Calostropis gigantea) widuri fiber is a fiber that comes from the thistle plant which can be taken from the widuri seed, the fiber from this widuri seed is very fine so it is suitable for use as textile materials. The purpose of this study was to analyze the mechanical properties of this thistle composite by using two tests, namely tensile and bending tests. The manufacture of this composite uses a resin base mixed with widuri stem fiber which has been soaked in 5% NaOH chemical liquid for 30 minutes with the same dimensions according to ASTM standards. The Tensile test refers to the ASTM D638 standard. The results of the tensile test have a tensile strength of 4.66 N/Keywords: Composite, Tensile Test, Compressive Test, Thistle Fiber, Epoxy Resin